2017
DOI: 10.2147/cia.s117637
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of person-centered care on people with dementia: a systematic review and meta-analysis

Abstract: BackgroundPerson-centered care is a holistic and integrative approach designed to maintain well-being and quality of life for people with dementia, and it includes the elements of care, the individual, the carers, and the family.AimA systematic literature review and meta-analysis were undertaken to investigate the effectiveness of person-centered care for people with dementia.MethodsLiterature searches were undertaken using six databases including Medline, EMBASE, CINAHL, PsycINFO, Cochrane Database, and Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
249
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(259 citation statements)
references
References 37 publications
(113 reference statements)
4
249
0
6
Order By: Relevance
“…In a systematic review of 19 interventional studies, person‐centered interventions showed effective reduction in BPSD and improved quality of life for individuals living with dementia . In particular, non‐pharmacological, person‐centered approaches can reduce behavioral challenges and psychotropic medication use for individuals living with dementia, reduce caregiver stress, and prevent harm to the individual or caregiver …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of 19 interventional studies, person‐centered interventions showed effective reduction in BPSD and improved quality of life for individuals living with dementia . In particular, non‐pharmacological, person‐centered approaches can reduce behavioral challenges and psychotropic medication use for individuals living with dementia, reduce caregiver stress, and prevent harm to the individual or caregiver …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In a systematic review of 19 interventional studies, person-centered interventions showed effective reduction in BPSD and improved quality of life for individuals living with dementia. 9 In particular, non-pharmacological, person-centered approaches can reduce behavioral challenges and psychotropic medication use for individuals living with dementia, reduce caregiver stress, and prevent harm to the individual or caregiver. 4,7,9,10 A robust and growing body of scientific evidence shows that music has positive emotional effects and physiological reactions, stimulating multiple areas of the brain that oversee emotion, mood control, motor skills, attention and memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…philosophy of care), making sure residents engage in meaningful activities, empowering care staff and changes in the physical environment (i.e. a more home‐like environment) (de Boer, Hamers, Zwakhalen, Tan, & Verbeek, ; Brownie & Nancarrow, ; Grabowski et al, ; Killet et al, ; Kim & Park, ; Koren, ; Te Boekhorst, Depla, De Lange, Pot, & Eefsting, ; Verbeek, van Rossum, Zwakhalen, Kempen, & Hamers, ). It is important to study both the actual person‐centredness of the care provided and these key values, attitudes, and behaviours to advance and improve the implementation of person‐centred care in care homes.…”
Section: Introductionmentioning
confidence: 99%
“…In the care setting, the valued concepts of preserving human dignity and autonomy in a compassionate manner, resonates with the construct of person-centered care -"the person comes first" [5]. Such constructs usually surface more prominently in end-of-life issues, especially in cancer palliative care but also arise in dementia care [6]. Dementia care, including the dementia day care setting, end-of-life issues, extend over a long period of time.…”
Section: Introductionmentioning
confidence: 99%